(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Diabetes mellitus (DM) is an important public health problem worldwide and its prevalence is increasing in developing countries. Family members of patients with diabetes are at an increased risk of developing the disease by 30 %–70 %. The identification of risk factors associated with susceptibility to diabetes has become relatively significant. Even in the absence of diabetes mellitus, individuals who are first-degree relatives (FDR) of diabetic subjects have both β-cell dysfunction and insulin resistance (IR). Aim & Objectives: The aim of this study is to identify the role of inflammation in the development of insulin resistance in the First degree relatives of diabetic and non-diabetic subjects. Methods: This cross-sectional study was conducted among first-degree relatives of type 2 diabetic families (FDR-DF) (n = 50) and first-degree relatives of non-diabetic families (FDR-nDF) (n = 50) at the ACS Medical College & Hospital in Chennai, Tamil Nadu, from January 2019 to December 2019. Parameters such as C-reactive protein, fasting blood glucose (FBS), postprandial blood glucose (PPBS), homeostasis model assessment—beta cell function (HOMA-β), and homeostasis model assessment—insulin resistance (HOMA-IR) were assessed in 100 FDR participants. Body mass index (BMI) and waist circumference (WC) were measured. Results: The prevalence rates among participants were 44% prediabetic, 24% diabetic, and 32% normal. HOMA-IR, CRP, and BMI were highly significant in the FDR-DF group compared to the FDR-nDF group. CRP level was highly correlated with HOMA-IR, HOMA- β and BMI (P= <0.01). Conclusion: The inflammatory marker hs-CRP is highly correlated with HOMA-IR and body mass index in first-degree relatives in diabetic families (FDR-DF). Thus, increased hs-CRP levels cause an increase in the HOMA-IR level, which in turn leads to insulin resistance and the development of prediabetes in the FDR-DF.